Assessment of nonlinear optical properties of polyurethane/MgO nanocomposites - Marzieh Nadafan; Rasoul Malekfar; Zahra Dehghani; Mohammad Allahabadi (Engineering and Technology Journal, 2015)
The third-order optical nonlinearities of polyurethane open cell (PUOC)/MgOnanocomposites, dissolved in dimethylformamide are characterized by Z-scan technique with continuous-wave (CW) Nd:YAG laser at its second harmonic frequency of 532 nm with TEM00 Gaussian profile. The synthesized samples are also characterized by scanning electron microscopy imaging. The nonlinear refractive indices and nonlinear absorption coefficients of the synthesized samples are obtained in the order of 10-8 cm2/W with negative sign and 10-5 cm2/W, respectively. The origin of optical nonlinearity in this case may be attributed due to the presence of strong saturable absorption effect. All the results suggest that the nonlinear coefficients of the synthesized samples can be controlled by the nanoparticles contents into PUOC. Furthermore, the results show that PUOC/MgO may be helpful candidate for the application in nonlinear optical field in the visible region.